Analisis Pegaruh Kebijakan Pajak, Norma Subjektif dan Kinerja Keuangan terhadap Kepatuhan Pajak UMKM di Kota Semarang - Patria Nurmala Oktafia; Hardiwinoto Hardiwinoto; Andwiani Sinarasri; Ayu Noviani Hanum (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
Taxes play a vital role as the primary source of state revenue and a key instrument for financing national development through the State Budget (APBN). This study aims to analyze the determinants of tax compliance among Micro, Small, and Medium Enterprise (MSME) taxpayers in Semarang City, with a particular focus on the effects of tax policy, subjective norms, and financial performance. A quantitative associative approach was employed, using primary data collected through questionnaires distributed to 100 MSME taxpayers selected via purposive sampling. The data was analyzed using the Partial Least Squares (PLS) method with WarpPLS software. The results indicate that tax policy and subjective norms have a positive and significant effect on MSME tax compliance, while financial performance shows no significant effect. The adjusted R² value reveals that the model explains 87.2% of the variance in taxpayer compliance. To enhance MSME tax compliance, the government should simplify tax regulations, strengthen social norms through education and community engagement, and ensure consistent, transparent, and fair implementation of tax policies